Advanced quantification of the site-occupancy in ordered multi-component intermetallics using atom probe tomography. (June 2022) - Breen, A.J.; Theska, F.; Lim, B.; Primig, S.; Ringer, S.P.
Abstract: A new experimental method is proposed to quantify the site-occupancy of substitutional solute elements in multi-component intermetallics from atom probe tomography data and is applied to the L12 ordered γʹ phase in the top, middle and bottom regions of an electron powder bed fusion produced IN-738LC build. Ti, W and Ta are found to substitute almost exclusively for the β sites. Cr and Mo show mixed behaviour with a higher proportion substituting for the β sites. Co also shows mixed behaviour but with a higher proportion substituting for the α sites. While γʹ maintains an almost constant chemistry and site-preference behaviour throughout the build, the relative site-occupancy ratio is observed to change, particularly for Co and Mo. The results suggest that local changes in thermal history inherent to metal additive manufacturing processes may induce changes to the resultant site-occupancy of γʹ. The method described here improves the experimental quantification of the local atomic site-occupancy, enabling an assessment of the substitutional solute element fractions occurring at the α and β sites in L12 ordered structures. This is important in multi-component intermetallics because of the burgeoning interest in relating the elastic and plastic properties of these structures to their site-occupancy. Graphical abstract: Image 1 Highlights: L12 γ′ in top, middle, and bottom regions of AM E-PBF IN738 characterised using APM. High-signal species-specific spatial distribution maps (SDMs) generated along ordered 002 and 022 planes. α-sites preferred by Ni and Co, other species exhibit β-site preferences. Gaussian fitting used to quantify ordering parameter and site-occupancy ratios. Co & Mo site occupancy ratios change significantly throughout the build height.